PENGARUH LOGAM BERAT Cd, Pb TERHADAP PERUBAHAN WARNA BATANG DAN DAUN SAYURAN - Widowati, Hening (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2011)
Cd, Pb heavy metal absorption in aquatic vegetables: Genjer (Limnocharis flava), Kangkung air (Ipomoea aquatica Forsk) dan Selada air (Nasturtium officinale R. Br), studied to see the relationship with green figure scale. The research objective was to identify the accumulated Cd, Pb in the consumed organ vegetable, and their impacts to the levels of green figure scale. The research was undertaken by planting three kinds of the aquatic vegetables to the contaminated pure Cd,pure Pb media, mixture of Cd and Pb with factorial randomized block design. Data were analyzed by factorial One-Way Anova and further test of Duncan and HSD to see the difference of Cd, Pb and green figure scale, regression and correlation to know the contribution of Cd, Pb in influencing the green figure scale. Variety of vegetables, media, organ, and the interaction influences the accumulation of Cd, Pb and level of green figure scale. There is a relationship between Cd, Pb metal accumulation to the level ofÂ green figure scale of the aquatic vegetables, with negative correlation that Cd, Pb decreased the vegetable green figure scale.Keywords: the influence of Cd, Pb; aquatic vegetables; green figure scale